Choosing Our Own Pathway to Competency-Based Undergraduate Medical Education. (January 2019) - Veale, Pamela; Busche, Kevin; Touchie, Claire; Coderre, Sylvain; McLaughlin, Kevin
Abstract : After many years in the making, an increasing number of postgraduate medical education (PGME) training programs in North America are now adopting a competency-based medical education (CBME) framework based on entrustable professional activities (EPAs) that, in turn, encompass a larger number of competencies and training milestones. Following the lead of PGME, CBME is now being incorporated into undergraduate medical education (UME) in an attempt to improve integration across the medical education continuum and to facilitate a smooth transition from clerkship to residency by ensuring that all graduates are ready for indirect supervision of required EPAs on day one of residency training. The Association of Faculties of Medicine of Canada recently finalized its list of 12 EPAs, which closely parallels the list of 13 EPAs published earlier by the Association of American Medical Colleges, and defines the "core" EPAs that are an expectation of all medical school graduates. In this article, the authors focus on important, practical considerations for the transition to CBME that they feel have not been adequately addressed in the existing literature. They suggest that the transition to CBME should not threaten diversity in UME or require a major curricular upheaval. However, each UME program must make important decisions that will define its version of CBME, including which terminology to use when describing the construct being evaluated, which rating tools and raters to include in the assessment program, and how to make promotion decisions based on all of the available data on EPAs.